The economic impact of pressure ulcers among patients in intensive care units. A systematic review. Issue 2 (May 2021) - McEvoy, Natalie; Avsar, Pinar; Patton, Declan; Curley, Gerard; Kearney, Cathal J.; Moore, Zena
Abstract: Background: The incidence and prevalence of pressure ulcers in critically ill patients in intensive care units (ICUs) remain high, despite the wealth of knowledge on appropriate prevention strategies currently available. Methods: The primary objective of this systematic review was to examine the economic impact of pressure ulcers (PU) among adult intensive care patients. A systematic review was undertaken, and the following databases were searched; Medline, Embase, CINAHL, and The Cochrane Library. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines was used to formulate the review. Quality appraisal was undertaken using the Consensus on Health Economic Criteria (CHEC)-list. Data were extracted using a pre-designed extraction tool, and a narrative analysis was undertaken. Results: Seven studies met the inclusion criteria. Five reported costs associated with the prevention of pressure ulcers and three explored costs of treatment strategies. Four main PU prevention cost items were identified: support surfaces, dressing materials, staff costs, and costs associated with mobilisation. Seven main PU treatment cost items were reported: dressing materials, support surfaces, drugs, surgery, lab tests, imaging, additional stays and nursing care. The overall validities of the studies varied between 37 and 79%, meaning that there is potential for bias within all the included studies. Conclusion: There was a significant difference in the cost of PU prevention and treatment strategies between studies. This is problematic as it becomes difficult to accurately evaluate costs from the existing literature, thereby inhibiting the usefulness of the data to inform practice. Given the methodological heterogeneity among studies, future studies in this area are needed and these should use specific methodological guidelines to generate high-quality health economic studies. Highlights: Costs for the prevention and treatment of pressure ulcers have increased significantly. There is a significant difference in the cost of pressure ulcer prevention and treatment strategies in ICU patients. Future studies in this area are needed and these should use specific methodological guidelines to generate high-quality health economic studies. The difference in reporting of cost and treatment items is problematic as it becomes difficult to accurately evaluate costs to inform management and staff members of health care organizations.